The Effect of Supervision, Work Motivation, and Interpersonal Communication on Employee Performance and Organizational Commitment as Variables Intervening - Suarni Norawati; Amir Lutfi; Zulher Zulher; Zamhir Basem (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Performance is a result that can be achieved by an individual at a certain time. Many factors can affect employee performance, but this study only aims to see the effect of supervision, work motivation and personal communication on performance and moderated by organizational commitment. Design/methodology/approach: This research was conducted at PR Lutvindo Wijaya Perkasa by using as many as 137 employees as respondents in this study. The types of data used are primary data and secondary data, obtained by interviews, questionnaires and documentation. Findings: The results of this study conclude that supervision and motivation have a significant effect on employee performance, but interpersonal communication has no effect on organizational commitment. Then supervision and personal communication have no significant effect on performance, while motivation and organizational commitment have a significant effect on employee performance. Practical implications: The data analysis tool is Path Analysis using the Smart PLS Versi 3.00 program. Originality/value: This paper is original Paper type: Research paper